Platelet-rich plasma plus bioactive glass in the treatment of intra-bony defects: a study in dogs - Marcelo Diniz Carvalho; Fabrícia Ferreira Suaid; Mauro Pedrine Santamaria; Marcio Zaffalon Casati; Francisco Humberto Nociti Jr; Antonio Wilson Sallum; Enilson Antônio Sallum (University of São Paulo, 2011)
OBJECTIVE: This study was designed to evaluate, histomorphometrically, the association of platelet-rich plasma (PRP) and bioactive glass (BG) in the treatment of periodontal intrabony defects. MATERIAL AND METHODS: Nine mongrel dogs were included in the study. Three-wall intrabony defects were surgically created at the mesial and distal aspect of first mandibular molar and exposed to plaque accumulation for 1 month. The defects were randomly assigned to the groups: control, BG, PRP, PRP+BG. Dogs were sacrificed 90 days after the surgeries. The histometric parameters evaluated were: length of sulcular and junctional epithelium, connective tissue adaptation, new cementum, new bone, defect extension and area of new bone filling the defect. RESULTS: A superior area of new bone was observed in PRP+BG and BG (13.80±2.32 mm² and 15.63±2.64 mm², respectively) when compared to the other groups (8.19±1.46 mm² and 8.81±1.47 mm² for control and PRP, respectively). No statistically significant differences were observed in the remaining parameters. CONCLUSIONS: Within the limits of this study, it may be concluded that PRP failed to provide statistically significant improvements in the histometric parameters.